Community Care Service Dalam Penanganan Lansia Terlantar Di Kabupaten Gorontalo Utara - Arsyad, Yolandika; Suleman, Syahputra Adisanjaya; Rahmawati, Rahmawati (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM), Sekolah Tinggi Ilmu Sosial dan Ilmu Politik (STISIPOL) Candradimuka, 2025)
Elderly individuals, defined as those aged over 60, are a vulnerable population within society. They are particularly susceptible to neglect due to declining physical and social functions, leading close family members to perceive them as burdens. Consequently, social services for the elderly are categorized into institutional and non-institutional care. The concept of community care is a form of non-institutional social service that involves community participation in addressing the issues faced by the elderly. This study aims to analyze the activities of the